Responsivitas Harga Saham Properti Terhadap Dinamika Ekonomi Moneter di Indonesia: Pendekatan Error Correction Model - Florentinus Nugro Hardianto (Economic Journal of Emerging Markets, 2006)
This study is an effort to extend reseach in stock market espicially about the Response of the price of stock to change monetary sector in Indonesia by using monthly data over the period 2002-2005. The price of stock is the stock price index of property and the monetary variables consist of the exchange rate, three months SBI, Indonesian money supply M2. The research applies Engle-Grange Error Correction Model.This study shows that there is a long run relationship between price stock of property and monetary variables. The second, in the short run the price of stock is affected significantly by money supply M2 and the US time deposit interest rate. Finnally, three months SBI, money supply M2 and the US time deposit interest rate influence the price of stock in the long rung.Key words: price stock of property, monetary variable, Engle-Granger Error Correction Model